Duloxetine Add-On to Risperidone for Treatment of Negative Symptoms in Patients with Stable Schizophrenia: Randomized Double-Blind Placebo-Controlled Study - Nikbakhat, M.-R.; Arabzadeh, S.; Zeinoddini, A.; Khalili, Z.; Rezaei, F.; Mohammadinejad, P.; Ghaleiha, A.; Akhondzadeh, S. (Pharmacopsychiatry, 2016)
Introduction: Although the pathogenesis of symptoms of schizophrenia is largely unknown, a variety of neurotransmitters are implicated, including serotonin and norepinephrine. Here we investigate the effectiveness of duloxetine as a serotonin-norepinephrine inhibitor in the treatment of negative symptoms.Methods: We performed a double-blind clinical trial on 64 patients with stable schizophrenia and no prominent symptoms of depression. Patients received risperidone (up to 6 mg/day) plus either duloxetine (60 mg/day) or placebo. Psychotic symptoms were assessed by the Positive and Negative Syndrome Scale (PANSS) at the onset of the trial, and at 2, 4, 6 and 8 weeks of therapy.Results: Compared to the placebo group, the duloxetine group showed significantly higher improvement in negative symptoms (p<0.001), PANSS total (p<0.001), and the general psychopathology subscale scores (p=0.001), but no significant difference in positive symptoms (p=0.13). The side effect profiles of the 2 treatment regimens were not significantly different.Discussion: Duloxetine adjuvant to risperidone seems to be a tolerable and efficacious treatment for primary negative symptoms of schizophrenia.
Keywords: duloxetine; SNRI; schizophrenia; clinical trial